# Prove that (cot x)' = - csc^2 x

hala718 | Certified Educator

calendarEducator since 2008

starTop subjects are Math, Science, and Social Sciences

Let f(x) = cotx

Then we know that: cot x = cosx/sinx

==> f(x) = cosx/sinx

Let us differetiate using the chain rule:

f(x) = u/v   such that:

u= cosx  =-=> u' = -sin

v= sinx ==>...

(The entire section contains 104 words.)

check Approved by eNotes Editorial

neela | Student

To prove that (cotx)' =  -cosec^2 x

Proof:

LHS = (cotx)' = (cosx/sinx)'

(cotx)' = {(cosx)'(sinx)- (cosx)(sinx)'}/(sinx)^2, as (u(x)/v(x))' = {u'(x)v(x)-u(x)v'(x)}/(v(x))^2.

(cotx)' = {(-sinx)(sinx) -cosx)(cosx)}/(sinx).

(cotx)' =  -(sinx^2x+cos^2x)/(sin^2x) .

(cotx)' = -1/sin^2x, as sin^2x+cos^2x = 1 is an identity.

(cotx)' = - cosec^2x.

So (cotx)' = - cosec^2x is proved.

giorgiana1976 | Student

We know that cosec x = 1/sin x and cot x = cos x/ sin x

If we have to calculate the derivative of cot x, we'll consider the quotient rule:

(cos x/sin x)' = (cos x)'*(sin x) - (cos x)*(sin x)'/(sin x)^2

We'll calculate the derivatives of the functions sine and cosine:

(cos x)' = -sin x

(sin x)' = cos x

(cot x)' = [(-sin x)*(sin x) - (cos x)^2]/(sin x)^2

(cot x)' = - [(sin x)^2 + (cos x)^2]/(sin x)^2

But, from the fundamental formula of trigonometry, we'll have:

[(sin x)^2 + (cos x)^2] = 1

(cot x)' = -1/(sin x)^2

But 1/sin x = csc x.

If we'll raise to square both sides, we'll get:

1/(sin x)^2 = -(csc x)^2